Production of pyrolytic oil for enhanced oil recovery - Goh, Meng Seng; Awang, Mariyamni; LimXin, Yi; Ani, Farid Nasir (2006)
In enhanced oil recovery (EOR), the objective of chemical flooding is to recover additional oil after a waterflood. However, chemical flooding is not widely applied in the oil fields due to the high cost of chemicals. The goal of this study is produce pyrolytic oil from oil palm shell as enhanced oil recovery additive. Oil palm shell as a solid waste from the palm oil industrs was converted into liquid oil by a fast bed pyrolytic process. The pyrolysis oil was collected in ice– cooled collector. The chemical compositions of the pyrolysis oil were then analyzed by Gas Chromatography – Mass Spectrometry (GC – MS). The chemical composition of pyrolysis oil was complex, comprising of mainly phenolic compounds, carboxylic acids and aldehydes. The physical properties of pyrolysis oil were also carried out. The phenolic compounds were further separated from the pyrolysis oil by liquid-liquid extraction using alkali and organic solvent. The extracted phenol fractions were analyzed by the Fourier Transform Infra-red (F.T.I.R) spectroscopy. Those phenolic compounds can be used as a starting material in the development of chemicals for enhanced oil recovery because they are inexpensive, high recoverability, and the most important thing is, they are not petroleum derivatives.